ANALISIS TINDAK TUTUR ILOKUSI DALAM IKLAN LAYANAN MASYARAKAT DI INSTAGRAM @DINKESJABAR - Wulansari; Via; Meylani, Yesi (IKIP Siliwangi, 2025)
This research is motivated by people's mistakes in interpreting information. The problem discussed is about the delivery of information through the form of illocutionary speech acts contained in uploaded images or photos on Instagram. The purpose of this study is to determine the type and meaning of illocutionary speech acts found. The research method used is descriptive qualitative with the research subject in the form of public service advertisement uploads on Instagram @dinkesjabar. The analysis techniques used are documentation techniques and observation techniques. Based on the results of the analysis, the types of directive illocutionary speech acts are found with the meaning of orders, instructions, suggesting, teaching, directing, and telling. Then it is emphasized by the discovery of imperative, declarative, and interrogative sentences. The conclusion of this research is that illocutionary speech acts in public service advertisements have different illocutionary meanings, each utterance in the form of information conveyed wants the speech partner/reader/society to do something.